ISSUES OF LANGUAGE AND SPEECH AT UZBEK TRANSLATORS - Boshmanova Dildora Maxram qizi (Journals Park Publishing, 2022)
This article discusses the work of the famous scientist, Doctor of Philology, Professor Nizamiddin Makhmudov, who made a worthy contribution to the development of linguistics.
Keywords: language, culture, linguistic, speech, cultural linguistics, psycholinguistics, paradigm.